Physical Activity Models to Maintain Physical Fitness Based on Simple Devices During the Covid-19 Pandemic For Adolescents - Hana Hafiza; Hernawan; Moch. Asmawi; Ayu Purnama Wenly (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2023)
Keeping fit is very important during the COVID-19 pandemic. Study aims to maintain fitness during the COVID-19 pandemic based on simple tools. The research subjects were 16 teenagers who live in Kimia Farma II Complex, Duren Sawit District. The research instrument used the Multi Stage Fitness Test (MSFT). In this study, the results of the pre-test for girls showed that the highest score was 29.5 ml/kg/minute, the lowest value was 22.8 ml/kg/minute, the mean was 25.8 ml/kg/minute. The results of the pre-test for boys showed that the highest score was 30.6 ml/kg/minute, the lowest value was 24.4 ml/kg/minute, the mean was 27. The results of post-test girls obtained the highest result 31.8 ml/kg/minute, the lowest value 23.6 ml/kg/minute, Mean 27.5. The results of the post-test for boys obtained the highest result of 33.6 ml/kg/minute, the lowest value of 27.2 ml/kg/minute, the mean 29.8. Paired Sample T-Test for girls and boys obtained the value of Sig. (2-tailed) of 0.000 < 0.05, it was concluded that there was an average difference between the pre-test and post-test of adolescent girls and boys. These findings indicate that the physical activity model for maintaining simple tool-based fitness during the COVID-19 pandemic for adolescents has a significant effect on physical fitness.